Synergistic Effect of Organic Silicon Surfactant in Chemical Control of the New Invasive Mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) in China - Huang, Jun; Zhang, Juan (Asian Journal of Chemistry, 2012)
The mealybug Phenacoccus solenopsis has been recently reported as one of the most serious invasive insect pests in Asian countries, such as Pakistan, India, Thailand, Australia and China. However, a safe and effective method of chemical control for the solenopsis mealybug is imminent. This study investigated the synergistic effects of 0.03, 0.06 and 0.09 % organic silicon surfactant on the 10 % imidacloprid WP against the mortalities of different instars nymph and adult female of the solenopsis mealybug. Results showed that both concentrations of organic silicon surfactant and insect stages had significantly effects on the mortality of the solenopsis mealybug. In addition, we found the suitable concentration of organic silicon surfactant adding to imidacloprid was 0.06 %. With the treatment of mixtures of 50 mg L-1 imidacloprid with 0.06 % organic silicon, the mortality of the solenopsis mealybug was up to 100 % after 15 d on the plants of Torenia fournieri.